Effect of salt form and processing method on salt intake and beef cattle performance - Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station, 2011)
Processing method (evaporated vs. rock) had no effect on salt consumption or weight gain of growing stocker cattle. Steers consumed 2.18 times more loose salt than block salt.
Keywords: Beef; Salt; Intake; Performance